Analysis of the current state of the mining industry - O.M. Syomak (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research and analysis of the branches of the national economy allows us to get operative data on tendencies and directions of development of different spheres of economy. The current state of development of industries is characterized on the basis of the study of statistical materials, the analysis of negative phenomena in the development and location of industrial production, the assessment of technical level and economic efficiency. The mining industry is the basis for the manufacturing industries, so it plays important role in the country's economy. The state and development of the extractive industry is closely linked to the state and development of the entire economy of the country. The article analyzes the state and dynamics of development of the extractive industry of Ukraine from 2013 to 2018 by the main economic indicators. The analysis is based on the processing of statistics on the object of study, the calculation of the main indicators of the industry and summarizing the findings, in order to identify the main problems and trends in the mining industry. The author analyzes the extraction of such industries as: coal, natural gas, iron ores, gypsum and anhydrite, limestone, chalk, sand, gravel, kaolin, peat and salt. After analyzing the peculiarities and problems of development of the mining industry, it was found that it is adversely affected by the unstable economic and political situations. Thus, solving the problems that are taking place in Ukraine's mining industry requires a comprehensive approach to the modernization of the industry's material base and reform of the mining sector development management system. The state should develop programs for the development of the extractive industry and encourage investment.